(Plus sign, minus sign, equals sign, division sign, multiplication sign) : tour collection [compact disc] - Sheeran, Ed, 1991- (Atlantic, 2024)
This album brings together some of the biggest songs Ed Sheeran has been performing on his tour from his decade-spanning mathematical album era. The set features performances of 22 studio tracks in all, including favorites such as Perfect; Shape of You; Photograph; and more.